Inventarisasi Bio-Ekologi Terumbu Karang Di Pulau Panjang, Kabupaten Jepara, Jawa Tengah - Suryono Suryono; Munasik Munasik; Raden Ario; Gentur Handoyo (Universitas Diponegoro, 2017)
The inventarization of coral bioecology is highly needed to identify the real condition of the observed coral, as a database in ecosystem management, as well as an attempt to rehabilitate critical coastal area. Coral condition valuation is conducted by counting the percentage of live coral coverage, by using the Line Intercept Transect method. This research shows that coral condition in Panjang Island falls into moderate category (with 29-49% of live coral coverage), which represent up to 57% from total observed area. Coral that falls under